Videography Reveals In-Water Behavior of Loggerhead Turtles (Caretta caretta) at a Foraging Ground - Patel, Samir H.; Dodge, Kara L.; Haas, Heather L.; Smolowitz, Ronald J. (Frontiers in Marine Science, 2016)
Assessing sea turtle behavior at the foraging grounds has been primarily limited to the interpretation of remotely-sensed data. As a result, there is a general lack of detailed understanding regarding the habitat use of sea turtles during a phase that accounts for a majority of their lives. Thus, this study aimed to fill these data gaps by providing detailed information about the feeding habits, prey availability, buoyancy control and water column usage by 73 loggerhead turtles across 45.7 hours of video footage obtained from a remotely operated vehicle (ROV) from 2008 – 2014. We developed an ethogram to account for 27 potential environmental and behavioral parameters. Turtles were filmed through the entire water column and we quantified the frequency of behaviors such as flipper beats, breaths, defecations, feedings and reactions to the ROV. We used the ROV’s depth sensor and visible cues (i.e. water surface or benthic zone in view) to distinguish depth zones and assess the turtles’ use of the water column. We also quantified interactions with sympatric biota, including potential gelatinous and non-gelatinous prey species, fish (including sharks), marine mammals and other sea turtles. We discovered that turtles tended to remain within the near surface and surface zones of the water column through the majority of the footage. During benthic dives, turtles consistently exhibited negative buoyancy and some turtles exhibited a dichotomous foraging behavior, first foraging within the water column, then diving to the benthic environment. Videography allowed us to combine behavioral observations and habitat features that cannot be captured by traditional telemetry methods, resulting in a broader understanding of loggerheads’ ecological role in the U.S. Mid-Atlantic.